Effects of Tai Chi and Resistance Band Training on Elderly’s Balance and Strength - Nontakhod, Kritpech; Chuaibunchum, Jeerawat; Klaharn, Choktawee; Phunsang, Netiphog (Physical Education Theory and Methodology, 2022)
Study purpose. The research aimed to study the effects of tai chi and resistance band training on elderly’s balance and strength. Materials and methods. The participants were 40 elderly females aged 62 to 76. They were selected by systematic random sampling, using balance score as the criterion. They were divided into two equal groups of 20 people each, namely, the Tai Chi and resistance band training (TCR) experimental group was trained for 8 weeks, 3 days a week for 60 minutes each day, and the control group (C) was not trained. The participants volunteered to sign the consent forms to participate in this research. Quantitative data was collected by measuring balance, hand muscle strength, and leg muscle strength. Qualitative data was collected via interviews and participant observation. Results. The research found that (1) balance, hand muscle strength, and leg muscle strength were no different before the training. Post-training of Tai Chi and resistance band trainings (TCR) of the 4th and the 8th weeks, the experimental group had the mean of balance, hand muscle strength, and leg muscle strength better than the pre-training and the differences between the experimental group and the control group were statistically significant (p<0.05). (2) The experimental group had balance, strength, good flexibility, relaxed body and good mental health. Conclusions. As regards the benefits to the physical fitness, tai chi and resistance band training (TCR) and combination exercise improve balance, hand muscle strength and leg muscle strength. This makes the elderly have good health and physical fitness.